Impact of Firm’s Fundamentals on Return of Stocks in Nepal - Pitambar Lamichhane; Bashu Dev Dhungel (MASI Mandiri Edukasi, 2024)
Return on stock is the chief concern of firm investors. Investors prefer better stock returns, and management focuses on increasing stock returns for wealth maximization. Internal factors are the firm fundamentals, and external factors are various macroeconomic variables that influence stock returns. This paper uses descriptive and causality research designs to examine the impact of firm fundamentals on stock returns in Nepal for the fiscal year 2007/08-2021/22. In this paper, the dependent variable is stock return and firm fundamentals such as earnings per share (EPS), book-to-market equity (BME), size of market value of equity (lnME), cash flow yields (CFY), and earning yield (EY) are used as explanatory variables. The correlation result shows that EPS, BME, and EY have positive relationships, and lnME and CFY have negative relationships with stock returns. The regression results reveal the positive impact of EPS, BME, and EY on stock returns in Nepalese firms. This indicates that higher EPS, BME, and EY lead to increased firms’ stock returns. Further, the result reports that lnME and CFY have an inverse influence on returns. Finally, the finding concludes that earnings per share, book-to-market equity, size of market value equity, and cash flow yields are strong, but earnings yield has a weak impact on the stock returns of firms in Nepal. Policymakers, investors, and academicians can implement the findings of this study for effective formulation and application of policies, maximize stock returns, and research activities.